099 Thrombotic and haemorrhagic complications associated with PLEX, reducing the risks. Issue 9 (12th August 2022) - Japzon, Nicole; Han, Ruth; Sacks, Benjamin; Levee, Viva; Rosser, Sinead; Samaroo, Yasmine; Westwood, John Paul; Zambreanu, Laura; Lunn, Michael P; Spillane, Jennifer
Abstract : Background: Plasma Exchange (PLEX) is an increasingly used therapy for various immune-mediated neu- rological diseases. Treatment can be complicated by potentially life-threatening clots and bleeds but there is limited data available regarding these risks. Method and Intervention: A retrospective audit of the records of patients receiving PLEX in the NHNN for neurological disease from May 2019 – October 2020 was performed to identify thrombotic and haemor- rhagic complications. A multi-disciplinary PLEX working group was created to set guidelines for all aspects of the PLEX process including mode of vascular access, use of prophylactic heparin and fluid replace- ment. The service was subsequently re-audited. Results: 46 patients were treated with plasma exchange between May 2019 and Oct 2020. 11% developed a thrombus requiring anticoagulation. 41% developed a haemorrhage, 42% of which required intervention. Following protocol change a review of 32 patients between November 2020 to October 2021 showed that there was a reduction of 27% in the incidence of thrombus and a 17% reduction in the incidence of haemorrhage. Conclusion: PLEX is integral to the treatment of disabling and potentially fatal immune-mediated neuro-logical diseases. Careful consideration of all aspects of the PLEX process, reduces risks associated with treatment and improves patient safety.